Antioxidant activities of isoflavones from the rhizomes of Belamcanda chinensis on carbon tetrachloride-induced hepatic injury in rats - Jung, SH; Lee, YS; Lim, SS; Lee, S; Shin, KH; Kim, YS (PHARMACEUTICAL SOC KOREA, 2004)
The present study was carried out to clarify whether tectorigenin and tectoridin isolated from the rhizomes of Belamcanda chinensis (Iridaceae) inhibit hepatic damage induced by carbon tetrachloride (CCl4)-intoxication in rats by the experimental methods in vitro and in vivo. Tectorigenin and tectoridin exhibited a significant decrease in serum transaminase activities elevated by hepatic damage induced by CCl4-intoxication in rats, as well as in a lipid peroxidation causing a significant decrease in malondialdehyde (MDA) production by thiobarbituric acid (TBA)-reactant assay. Both compounds also showed strong increase in the antioxidant enzymes such as hepatic cytosolic superoxide dismutase (SOD), catalase and glutathione peroxidase (GSH-px) activities in CCl4-intoxicated rats. These results suggested that tectorigenin and tectoridin isolated from the rhizomes of B. chinensis possess not only the antioxidative, but also the hepato protective activities in CCl4-intoxicated rats.
Keywords: SUPEROXIDE-DISMUTASE; KAIKASAPONIN-III; TECTORIGENIN; MECHANISMS